2017
DOI: 10.1080/09540105.2017.1313819
|View full text |Cite
|
Sign up to set email alerts
|

Honey and quercetin reduce ochratoxin A-induced DNA damage in the liver and the kidney through the modulation of intestinal microflora

Abstract: This study was conducted to evaluate the interactions between the gut microbiota, ochratoxin A and functional food such as honey and quercetin, and the consequences of these interactions on ochratoxin-induced DNA damage in blood, liver and kidney cells. Honey (2 g kg −1 ) or Quercetin (50 mg kg −1 ) was applied to mice by intragastric application every day for 15 days, immediately before ochratoxin treatment (100 µg kg −1 ). We investigated colonic probiotic bacteria count, β-glucuronidase activity, the alkali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 61 publications
(137 reference statements)
2
34
0
Order By: Relevance
“…Q is a member of the flavonoids family and it is well known that Q has wide bioactivity, including hypolipidemic and antioxidant properties. Previous studies have reported that Q showed a protective effect against the toxic effect of mycotoxins such as aflatoxin [ 156 , 157 ], OTA [ 158 , 159 , 160 ], T2 [ 161 ], zearalenone [ 162 , 163 ], and alternariol [ 164 ]. Round-shaped nanoparticles consisting of quercetin showed a protective effect on OTA-treated rats (3 mg/kg diet).…”
Section: Nano Approaches For Mycotoxin Risk Eliminationmentioning
confidence: 99%
“…Q is a member of the flavonoids family and it is well known that Q has wide bioactivity, including hypolipidemic and antioxidant properties. Previous studies have reported that Q showed a protective effect against the toxic effect of mycotoxins such as aflatoxin [ 156 , 157 ], OTA [ 158 , 159 , 160 ], T2 [ 161 ], zearalenone [ 162 , 163 ], and alternariol [ 164 ]. Round-shaped nanoparticles consisting of quercetin showed a protective effect on OTA-treated rats (3 mg/kg diet).…”
Section: Nano Approaches For Mycotoxin Risk Eliminationmentioning
confidence: 99%
“…We observed that exposure to low OTA doses induced substantial changes in the diversity and composition of gut microbiota. The unique study in mice used culture-dependent methods to investigate the effect of OTA on the growth of colonic probiotic bacteria [ 36 ]. This approach has great limitations since the majority of intestinal bacteria are widely considered to be unculturable and have never been isolated in the laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mouse is the most commonly used organism in basic and experimental research, only one study has investigated the effect of OTA on the growth of colonic probiotic bacteria in mice [ 36 ]. However, culture-dependent methods have limitations since the majority of intestinal bacteria are widely considered to be unculturable and have never been isolated in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Ganash, Mujallid, Al‐Robai, and Bazzaz () found that deleterious pathological effects of doxorubicin in mice (including effects on liver function) are ameliorated by co‐treatment with honey (5 ml kg −1 day −1 ). Oršolić, Jembrek, and Terzić () found that DNA damage in the liver and kidney induced by ochratoxin treatment (100 μg kg −1 day −1 ) in mice is reduced if the treatment is immediately preceded by administration of honey (2 g kg −1 day −1 ). In addition, Haron and Mohamed () observed that restraint stress in pregnant rats has adverse effects on testicular and epididymal weights and sperm parameters in male offspring, but these effects are reduced by administration of honey during pregnancy.…”
Section: Discussionmentioning
confidence: 99%